Surface settlement induced by horizontal directional drilling - Asif Ahmed; Md Azijul Islam; Md Zahangir Alam; Hashmi S. Quazi (Underground Space, 2023)
Horizontal directional drilling (HDD) is a widely used trenchless method for underground utility connections. The associated ground settlement triggered by HDD depends on the size, types, and surface texture of pipe, diameter of borehole, and soil conditions. The present study investigates the surface settlement due to the construction of a 1067 mm diameter HDD, which will replace an existing sewer siphon under the SR-60 highway in Chino, California using empirical, and numerical methods. Based on the results obtained from the subsurface investigation, an empirical analysis was conducted first. followed by numerical modeling of the HDD using PLAXIS 2D software. A careful comparison between two different methods indicated closer values of surface settlement between the empirical method (7.3 mm) and the numerical modeling (4.6 mm). In addition, the shape of surface settlement and horizontal settlement curves for the empirical and numerical methods was found to be similar. The minor discrepancy between the two methods resulted as the numerical model can host several soil layers whereas the empirical equation can use only one type of soil. Finally, a parametric study was conducted to evaluate the effect of borehole cover depth, size, and soil parameters on surface settlement. It was observed that soil strength parameters yielded a greater effect on surface movement, whereas modulus of elasticity has a relatively smaller influence with zero contribution from Poisson's ratio.